Nanosensors : Physical , Chemical and Biological - Khanna, Vinod Kumar (Boca : Raton C R C, 2012)
Bringing together widely scattered information, Nano sensors: Physical, Chemical, and Biological explores sensor development in the nanotechnology age. This easy-to-read book presents a critical appraisal of the new opportunities in the area of sensors provided by nanotechnologies and nanotechnology-enabled advancements. After introducing nano sensor classification and fundamental terms, the book outlines the properties of important nanomaterials and nanotechnologies used in nano sensor fabrication. Subsequent chapters are organized according to nano sensor type: physical (mechanical and acoustical, thermal and radiation, optical, and magnetic); chemical (atomic and molecular energies); and biological. The final chapter summarizes the current state of the field and discusses future trends. A complete and authoritative guide to nano sensors, this book offers up-to-date information on the fabrication, properties, and operating mechanisms of these fast and reliable sensors. It addresses progress in the field, fundamental issues and challenges facing researchers, and prospects for future development.
Includes bibliographical references; Index 603-637p.
Keywords: Detectors; Nanosensors; Nanostructured materials; Physics